Responsive and self-healing supramolecular photonic crystal hydrogels based on host–guest interactions. Issue 42 (13th October 2022) - Huang, Lingcong; Liu, Yang; Chen, Hongxiang; Wu, Jun; Zhang, Xiongzhi; Liu, Simin
Abstract : The development of supramolecular photonic crystal hydrogels (SPCHs) with responsive and self-healing properties has been established as an important topic. Abstract : The development of supramolecular photonic crystal hydrogels (SPCHs) with responsive and self-healing properties has been established as an important topic. Here, we show a 3D network SPCH prepared by dynamic host–guest interactions between the host molecule cucurbit[8]uril and guest units. This obtained SPCH exhibited a bright structural color due to the introduction of photonic crystal Fe3 O4 @C magnetic nanoparticles (Fe3 O4 @C MNPs). The responsive properties of the SPCH were studied to show that the structural color of the SPCH could be tuned by water content, ethanol and competitive guest concentration. The SPCH exhibited self-healing properties without the loss of structural color at room temperature, owing to the introduction of dynamic host–guest interactions. This work provides a novel method for producing responsive and self-healing SPCHs with various potential applications.